THE CULTURE OF THE RENAISSANCE IN EUROPE AND ITS MAIN CHARACTERISTICS - SAFAROVA Тumaris (Western European Studies, 2024)
By the end of the Middle Ages, the number of literate and educated people who read a lot, went on trips, could speak several languages, and were interested in philosophy, history, and art increased. They learned to appreciate the joys of life in this world, they looked at nature, society, and people in a new way. Supporters of a divine, secular, human view of the universe, not a church, call themselves humanists (Lat. - human). From this point of view, in this article, we classify the definitions given to the concept in various literature for the study of Renaissance culture in Europe
Keywords: Renaissance; humanism; reformation; Martin Luther